Financial Innovation And Annuity Concepts For Teens: Pembelajaran Interaktif Konsep Anuitas Untuk Mendorong Literasi Keuangan Siswa Di Kairatu - Lewaherilla, Norisca; Sinay, Lexy Janzen; Bakarbessy, Lusye (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
Low financial literacy among teenagers in rural areas is a challenge that needs to be addressed immediately. The FINACT (Financial Innovation and Annuity Concepts for Teens) program is designed as a form of community service that aims to introduce basic concepts of financial planning, especially annuities, through an interactive and contextual approach. This activity was carried out at SMP Negeri 5 Kairatu with discussion-based learning methods, simulations, and educational games. The results of the activity showed an increase in student participation and interest in financial topics, although there were obstacles in basic arithmetic skills. Communication of financial literacy with basic mathematics learning and an adaptive approach to student understanding are needed. The program shows potential as an initial step in forming a more financially capable young generation.